Uma análise da questão da adesão humana a crenças - Nagata, Paulo Tadao [UNESP] (2015)
Why do we have beliefs? What are the motivations that lead us to believe in things which have no empirical grounding in reality? The attempt to answer these questions will be the leitmotiv by which will guide this dissertation. Therefore its purpose will be to make an analysis of the problem of our voluntary adherence to beliefs, most specifically the religious beliefs. Preliminarily we will trace a brief history of the concept of belief and, from it, we will study the conflicting forces that are confronted within the human agent to the emergence of the will to believe. Among these forces, we will study the psychological conditions of heteronomy and autonomy as well as the emotions aroused by stories of fiction. We propose here, not a hostile confrontation with beliefs, but a philosophical enlightenment that can minimize the evils associated with these beliefs.